Clinical outcome and inflammatory response after transfusion of washed and unwashed red blood cells in children following cardiovascular surgery. (December 2017) - Busch, Christine; Pfitzer, Constanze; Raschzok, Sonja; Miera, Oliver; Berger, Felix; Schmitt, Katharina Rose
Abstract: Children frequently require red blood cell transfusion after cardiac surgery, which can generate an inflammatory response that is associated with increased morbidity and mortality. The aim of this study was to evaluate the inflammatory response and clinical effect of RBC transfusion in children. In a pediatric prospective controlled clinical trial 48 children were randomized to an unwashed or washed red blood cell transfusion group after cardiac surgery. Red blood cells were washed using an auto transfusion device with blood gas analyses of the packed red blood cells performed before transfusion. Vital parameters, blood analyses, and plasma concentrations of cytokines were measured before and 24 h after transfusion. Forty-five children were included with 23 receiving unwashed and 22 washed red blood cells. Washing reduced hemoglobin, potassium, and glucose while increasing sodium concentration in the packed red blood cells. Increased levels of hemoglobin, hematocrit, and erythrocyte counts were observed in both groups after transfusion. Increased levels of cytokine expression (IL-1α, IL-6, IL-8, MCP-1, and TARC) were detected in the group receiving unwashed red blood cells, while IL-8 levels were reduced in patients receiving washed red blood cells. Also, the percentage increase of cytokine concentrations (IL-6, IL-8, MCP-1, and GP-VI) before in comparison to after transfusion was lower in patients receiving washed red blood cells. No significant differences in clinical outcome parameters were observed between the two groups. Transfusion of red blood cells induces a pro-inflammatory reaction which can be diminished by washing the red blood cells before transfusion. Further clinical trials with larger patient cohorts receiving multiple transfusions are needed to better evaluate the clinical outcome. Highlights: Cytokine levels were increased in the group receiving unwashed red blood cells. Increase of cytokine was examined before and after transfusion. This increase was lower in patients receiving washed red blood cells. Transfusion of red blood cells induces a pro-inflammatory reaction. This reaction can be diminished by washing the red blood cells before transfusion.